Viabilidade de Staphylococcus Aureus (FRI361 e N315) e modulação da expressão de suas toxinas (SEC e TSST- 1) em queijo tipo frescal adicionado de lactobacillus rhamnosus (D1) e Weissella paramesenteroides (GIR1604*) - Gabriela Oliveira e Silva (2018)
Microbiological food standards are indicative of health quality and safety. Products that can cause harm to the consumer's health when they are applied. Staphylococcus spp. are strongly associated with foodstuffs transmitted through intoxication, caused by the action of their thermostableenterotoxins. Milk and its derivatives are one of the main foods related to staphylococcal intoxication due to the fact that Staphylococcus spp. are one of the main causes of bovine mastitis. Therefore, it is necessary to investigate alternatives capable of inhibiting the growth of Staphylococcus spp. in dairy products, as well as a production of its enterotoxins. Like lactic acid bacteria (BAL), components of the natural microbiota of raw milk, they are known to present antimicrobial potential against several pathogenic microorganisms, including Staphylococcus aureus. Thus, the present work had the objective of producing 81 cheeses in the laboratory under sterile conditions, adding combinations of S. aureus, producers of SEC (FRI361) and TSST-1 (N315) and Lactobacillus rhamnosus (D1) isolated from cheese Serra da Canastra and Weissella paramesenteroides (GIR16L4 *), isolated from raw milk, and to study the viability of S. aureus and its toxin-producing capacity in the presence of BAL. The cheeses were stored at 7 ° C andstored for 14 days. The experiment was delimited in a factorial scheme according to a 9x3 factorial scheme, with nine combinations of microorganisms and three storage times of the cheeses in three sreplicates. The experimental design was elaborated according to the factorial scheme 9x3, being nine combinations of microorganisms and three times of storage of the cheeses, in three replicates. Microbiological analyzes (counting of S. aureus and BAL), physical-chemical (moisture by the gravimetric method, nitrogen compounds by the Kjeldahl method, titratable acidity and pH) andmolecules (qPCR) were performed in three time periods (1, 7 and 14 days). Over the 14 days it was observed that the presence of BAL did not alter the growth of S. aureus. However, BAL is able to include an expression of toxins produced by S. aureus in cheeses. A modulation of the expression of secte and tsst-1 by N315 from the first day of analysis, an expression of FRI361 seg reduced from the analysis period, suggesting a strain-dependent modulation. These results are a company specialized in microbiota, capable of inhibiting an expression of staphylococcal and reduced toxins, as well as a possibility of an individual developed in staphylococcal intoxication.